Pengaruh Hambatan Samping terhadap Tingkat Pelayanan Ruas Jalan Elak Kota Lhokseumawe - Qamal, Qanitatul Isra; Sanjaya, Tegar; Azzahra, ?Aisyah Nayla; Yanza, Aliya Putri; Hamid, Bilal Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Lhokseumawe City Bypass Road is one of the national arterial routes that plays a strategic role as an alternative corridor connecting the Medan–Banda Aceh road. The development of activities along this road segment, such as educational areas, shops, restaurants, and religious facilities, has triggered an increase in roadside activities. These conditions generate side frictions in the form of on-street parking, pedestrian crossing activities, and vehicles entering and exiting adjacent areas, which have the potential to reduce traffic performance. This study aims to analyze the effect of side frictions on the capacity and level of service of the Lhokseumawe City Bypass Road. The research method uses a descriptive quantitative approach through field surveys conducted for seven consecutive days during morning to afternoon peak hours. The collected data include road geometric conditions, traffic volume, and the types and frequency of side frictions. The analysis is based on the Indonesian Road Capacity Guidelines (PKJI) 2014 to determine road capacity, degree of saturation, and level of service. The results show that side frictions have a significant effect on road segment performance, indicated by a reduction in capacity of approximately 20–35%. This impact causes the level of service to decline from category B (good) to category C (moderate). These findings emphasize the importance of managing roadside activities through parking management, control of access points, and increased public awareness in using road space in an orderly manner to maintain traffic performance.